Transcriptome Co-expression Network and Metabolome Analysis Identifies Key Genes and Regulators of Proanthocyanidins Biosynthesis in Brown Cotton - Wang, Zhenzhen; Zhang, Xiaomeng; He, Shoupu; Rehman, Abdul; Jia, Yinhua; Li, Hongge; Pan, Zhaoe; Geng, Xiaoli; Gao, Qiong; Wang, Liru; Peng, Zhen; Du, Xiongming (Frontiers in Plant Science, 2022)
Brown cotton fiber (BCF) is a unique raw material of naturally colored cotton. But characteristics of the regulatory gene network and metabolic components related to the proanthocyanidins biosynthesis pathway at various stages of its fiber development remain unclear. Here the dynamic changes in proanthocyanidins biosynthesis components and transcripts in the BCF variety ‘Zong 1-61’ and its white near isogenic lines ‘RT’ were characterized at five fiber developmental stages (0-, 5-, 10-, 15-, and 20- days post anthesis; DPA). Enrichment analysis of differentially expressed genes, comparison of metabolome differences, and pathway enrichment analysis of a weighted gene correlation network analysis together revealed the dominant gene expression of flavonoid biosynthesis, phenylpropanoid metabolisms and some carbohydrate metabolism at 15DPA or 20DPA than white cotton. Eventually, 63 genes were identified from five modules putatively related to flavonoid biosynthesis. Three R2R3-MYB and two bHLH transcription factors were predicted as the core genes. Further, GhANS, GhANR1 and GhUFGT2 were preliminarily regulated by GhMYB46, GhMYB6, and GhMYB3 respectively, According to yeast one-hybrid assays in vitro. Our findings provide an important transcriptional regulatory network of proanthocyanidins biosynthesis pathway and dynamic flavonoid metabolism profiles.